From ethics to ecology: How ethical leadership drives environmental performance through green organizational identity and culture - Jummah Rihal; Ahmad Alzubi; Hasan Yousef Aljuhmani; Ayşen Berberoğlu (PLoS ONE, 2025)
This study investigates how ethical leadership enhances environmental performance in manufacturing firms through the mediating role of green organizational identity (GOI) and the moderating role of green organizational culture (GOC). Grounded in the Resource-Based View (RBV) and Ecological Modernization Theory (EMT), the study develops an integrated framework that explains how leadership, identity, and culture jointly drive sustainability outcomes. Data were collected from 471 top management team members in Turkish manufacturing organizations and analyzed using structural equation modeling (SEM). The results indicate that ethical leadership positively affects environmental performance (β = 0.147, p = 0.009) and GOI (β = 0.381, p = 0.000). GOI, in turn, improves environmental performance (β = 0.359, p = 0.000) and mediates the leadership–performance link (β = 0.137, p = 0.000). The findings further demonstrate that GOC strengthens the impact of ethical leadership on GOI (β = 0.122, p = 0.000) and reinforces the GOI–performance relationship (β = 0.142, p = 0.000). Conversely, under low levels of GOC, the direct effect of ethical leadership on environmental performance weakens (β = −0.198, p = 0.000), underscoring culture as a boundary condition. These results advance RBV by highlighting ethical leadership as a strategic intangible resource and extend EMT by showing how identity and culture institutionalize ecological values. The study contributes theoretically by bridging RBV and EMT within a unified sustainability framework and provides practical guidance for managers to embed ethical leadership, identity, and culture into organizational practices to achieve superior environmental outcomes.